Identification of a Neutralizing Monoclonal Antibody That Recognizes a Unique Epitope on Domain III of the Envelope Protein of Tembusu Virus - Qu, Shenghua (Viruses, 2020)
Domain III of the envelope protein (EDIII) is the major target of flavivirus neutralizing antibody. To date, little is known regarding antibody-mediated neutralization of Tembusu virus (TMUV), a novel flavivirus emerging in duck in 2010. Here, a novel monoclonal antibody (MAb), designated 12F11, was prepared by immunization of mice with recombinant EDIII (rEDIII) protein. Using virus neutralization test, 12F11 in undiluted ascites neutralized the TMUV infectivity to induce the development of cytopathic effects in BHK-21 cells, indicating that 12F11 exhibits a neutralizing activity. The neutralizing activity of 12F11 was confirmed by plaque reduction neutralization test, in which 12F11 reduced significantly the number of plaques produced by TMUV in BHK-21 cells. Western blot analyses of a series of truncated rEDIII proteins showed that the epitope recognized by 12F11 includes amino acids between residues 8 and 77 of EDIII protein. Function analysis demonstrated that 12F11 neutralizes TMUV infection at virus adsorption and at a step after adsorption to a certain extent. The present study provides an important step towards elucidating antibody-mediated neutralization of TMUV.